Calibrating the AIDS and Multinomial Logit Models with Observed Product Margins - Gloria Sheu; Charles Taragin (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2012)
We show how observed product margins may be used in lieu of an observed market elasticity to calibrate parameters for two commonly used demand forms: the Almost Ideal Demand System (AIDS) and the multinomial logit. This technique is useful for antitrust practitioners interested in simulating the e ects of a merger, since estimates of product margins are often easier to obtain than estimates of market elasticities.
Keywords: L40; K21; 330; demand calibration; multinomial logit; almost ideal demand system; AIDS